(untitled) (Experimental biology, 2020)
The puberty is one of the most difficult periods of the formation of the body. It is this period that is characterized by morphological and functional rearrangements. Under the influence of sex hormones secreted by the body in large quantities, the neuroendocrine system is rearranged. Heavy training loads, information overstrain, emotional stress, disturbance of sleep and wakefulness, adverse environmental influences contribute to a negative shift of physiological parameters from normal. A prolonged stay in such conditions leads to a deviation of physiological functions from the norm, and, as a result, to a violation of the functions of the reproductive organs. The aim of this work was to study pituitary (LH, FSH), sex (testosterone, estradiol) and thyroid-stimulating (TSH) hormones in the blood of schoolgirls in the city of Almaty. Research was conducted at the Centre of Molecular Medicine. A comprehensive analysis of hormones was performed in 70 girls of the city of Almaty aged 12 to 16 years. The results were obtained by ELISA. The mean norm values ​​of FSH hormones were found to be 5.08 ± 0.19 IU / L, LH 5.14 ± 0.35 IU / L, LH / FSH 1.22 ± 0.03, Estradiol 13.6 - 190.4 pg / ml, testosterone 0.7 ± 0.07 ng / ml, TSH 2.06 ± 0.11 μI / l. Most of the examined schoolgirls showed deviations from the norm in the direction of increasing hormone and on average are LH 12.1 ± 0.53 IU / L, LH / FSH 2.52 ± 0.17, estradiol 395 ± 0.28 pg / ml, testosterone 2.99 ± 0.12 ng / ml, 3.7 ± 0.02 μMU / L. Identified deviations may be associated with adverse environmental conditions, since Almaty is on the list of the most polluted cities among the CIS countries. Key words: reproductive system, luteinizing hormone (LH), follicle-stimulating hormone (FSH), estradiol, testosterone, thyroid-stimulating hormone (TSH), ecology.